Prolonged Slow Expiration Technique and Gastroesophageal Reflux in Infants Under the Age of 1 Year - Lievens, Laure; Vandenplas, Yvan; Vanlaethem, Sylvie; Van Ginderdeuren, Filip (Frontiers in Pediatrics, 2021)
Background: The Prolonged Slow Expiration Technique (PSE) is used in infants with bronchial obstruction and hypersecretion to facilitate the removal of mucus from the respiratory tract. The effect of PSE on gastroesophageal reflux (GER) is not well documented. The aim of this study is to determine the influence of PSE on GER in infants under the age of 1 year. Methods: In this controlled trial with intra-subject design, infants were observed using multichannel intraluminal impedance-pH monitoring (MII-pH) over 24 hours. During monitoring, the participants received one 20 minute intervention of PSE in a supine position, 2 hours after feeding. The number of reflux episodes (REs) during PSE were compared to a 20 minutes period before and after PSE. Results: Fifty infants under the age of 1 year were screened of whom 22 had a pathological GER. For the entire group, there was no significant difference in the total number of REs between before, during, or after the PSE treatment (P = .76). In the group of infants with a 24-hr abnormal MII-pH result (n = 22), no significant difference in the total REs was found between the three measuring points as well (P = .59). Conclusion: PSE does not cause a significant difference in REs in infants under the age of one year.